Cultural Sidelining: How Campus Cultures across University Contexts Shortchange Working-Class Hispanic Students. (19th October 2021) - Garza, Alma Nidia
Abstract: As organizations that privilege the interests and behaviors of a White middle class, universities institutionalize processes that undermine both the preparation and contributions of students from working-class backgrounds and racial/ethnic minoritized groups such as Hispanics. While studies have documented how universities carry out forms of class or racial exclusion, how racial exclusion is embedded in university class cultural practices is less understood. Understanding how class processes that are linked to racial objectives inhibit Hispanic student development is important not solely due to the group's growing representation in college but also because such information facilitates an understanding of how universities legitimize racial hierarchies. Drawing on theories of racialized organizations and cultural reproduction, I compare how working-class Hispanic students attending a moderately selective institution and their co-ethnic counterparts attending a less selective, regional university contend with class cultural hierarchies that impact their growth and inclusion. I propose that universities engage in a practice of cultural sidelining. Students are unable to exercise elements of sidelined class cultures depending on the set of behaviors endorsed on campus. Sidelining enables organizations to draw on social class practices to carry out divergent forms of racial exclusion.